School monitoring: the use of video surveillance in the geography classes/O monitoramento do espaço escolar: a utilização de câmeras de vigilância nas aulas de geografia - Fernando Camillo Santos Cano (Universidade Estadual de Alagoas, 2020)
Contemporary society from the technical-scientific informational milieu has spread new technologies ensuring greater access to information and knowledge. The knowledge ensured the evolution and development of socioeconomic relations which at the same time imposed forms of surveillance and control over society. Security and surveillance cameras are increasingly present in people's daily lives, mainly, motivated by the culture of fear and insecurity, where being monitored is necessary to ensure human reproduction in the midst of deepening socio-spatial inequalities. Having as spatial clipping and insertion a private teaching network of the municipality of Rio Claro-SP objective is in this article to establish the reporting and characterization of the use of surveillance cameras during the teaching-learning process in geography classes. As from a qualitative and dialectical approach, using observation, description, understanding and meaning of knowledge analyze how the presence of video monitoring cameras hinder development, interaction and learning processes of middle school students. Therefore, the present study was conducted in locus in 2017, during the discipline of Supervised Internship IV of the Undergraduate Program of the Biosciences Institute of UNESP, Rio Claro-SP, Brazil.